2023
DOI: 10.1038/s41746-023-00804-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a smartphone application for blood pressure estimation in Bangladesh, South Africa, and Tanzania

Abstract: Undetected and unmonitored hypertension carries substantial mortality and morbidity, especially during pregnancy. We assessed the accuracy of OptiBPTM, a smartphone application for estimating blood pressure (BP), across diverse settings. The study was conducted in community settings: Gaibandha, Bangladesh and Ifakara, Tanzania for general populations, and Kalafong Provincial Tertiary Hospital, South Africa for pregnant populations. Based on guidance from the International Organization for Standardization (ISO)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A more recent study included obstetric women in Africa and Asia. The results demonstrated that BP measurements also fell within the ISO81060-2:2018 standards [43]. It should be noted that the studies described above did not report error grid analysis, with the exception of the study carried out during the induction of general anesthesia (the study contained a small amount of recorded BP in zone C, which indicated moderate risk for the patient).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A more recent study included obstetric women in Africa and Asia. The results demonstrated that BP measurements also fell within the ISO81060-2:2018 standards [43]. It should be noted that the studies described above did not report error grid analysis, with the exception of the study carried out during the induction of general anesthesia (the study contained a small amount of recorded BP in zone C, which indicated moderate risk for the patient).…”
Section: Discussionmentioning
confidence: 72%
“…Currently, there are only seven studies that have compared BP measurements collected with the OptiBP™ versus a non-invasive or invasive reference method. Three studies were carried out in Lausanne, Switzerland, by the inventors of the BP application [26,28,31], three other studies by our team in Belgium [27,29,30] and the last study was conducted as a tri-center study in South Africa, Tanzania, and Bangladesh [43]. These studies are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…51 52 Findings from this multi-site study demonstrated accuracy against International Organisation for Standardisation (ISO) benchmarks, including among pregnant populations, except in Bangladesh for systolic BP ISO criterion 2. 52 53 A similar validation study was also conducted in Indonesia among pregnant populations in West Lombok and East Lombok in West Nusa Tenggara Province. 54…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 96%
“…Furthermore, shortfalls in human resources and the need for targeted health interventions, such as in the areas of maternal health care and management of STIs, serve as key issues that have the potential to be addressed through the predictive capabilities offered by AI [ 14 ]. In addition, the use of AI to power “software as a medical device” [ 15 ] presents an opportunity to leapfrog access to diagnostic devices, such as ultrasounds [ 16 ] and blood pressure equipment [ 17 ]. This has also been seen with the emergence of contraceptive and fertility software applications [ 18 , 19 ], which are increasingly securing regulatory approvals from national authorities [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%